W obronie nauk europejskich i miejsca w nich filozofii - Drozdowicz, Zbigniew (Człowiek i Społeczeństwo, 2015)
The need for defending European sciences of attempts to imposing onto them American patterns of functioning is for me an obvious matter. This threat occurred already in the first decades of the last century (these were pointed out among others by Max Weber). Since then this process of americanization (called today implementing of the Bologna process) has increased, finding support within ministerial assemblies, deciding on the directions of development of these sciences, as well among scholars who’s research might be easily translated into practical applications. I do not claim that such research is not important for the progress of science. I do claim however that recognizing this research as the only one that matters and supporting them practically (for example through granting them a larger part of financial means) and depriving of the so called “philosophical core” is not just making them shallow but also an evidence for not understanding what science was, is and should be. I support my claims in this matter through the opinions of Edmund Husserl and Allan Bloom.